The potential of HEART score to detect the severity of coronary artery disease according to SYNTAX score - Amirhossein Salimi; Abdolali Zolghadrasli; Soodeh Jahangiri; Mohammad Reza Hatamnejad; Mehdi Bazrafshan; Peyman Izadpanah; Fatemeh Dehghani; Amir Askarinejad; Maryam Salimi; Hamed Bazrafshan Drissi (Scientific Reports, 2023)
Abstract Clinical scoring systems such as the HEART score can predict major adverse cardiovascular events, but they cannot be used to demonstrate the degree and severity of coronary artery disease. We investigated the potential of HEART Score in detecting the existence and severity of coronary artery disease based on SYNTAX score. This multi-centric cross-sectional study investigated patients referred to the cardiac emergency departments of three hospitals between January 2018 and January 2020. Data including age, gender, risk factors, comorbidities, 12-lead ECG, blood pressure and echocardiogram were recorded for all the participants. Serum troponin I level was measured on admission and 6 h later. Coronary angiography was done via the femoral or radial route. HEART and SYNTAX scores were calculated for all patients and their association was assessed. 300 patients (65% female) with mean age of 58.42 ± 12.42 years were included. mean HEART Score was 5.76 ± 1.56 (min = 3, max = 9), and mean SYNTAX score was 14.82 ± 11.42 (min = 0, max = 44.5). Pearson correlation coefficient was 0.493 between HEART Score and SYNTAX score which was statistically significant (P < 0.001). We found that HEART Score of more than 6 is 52% sensitive and 74.7% specific to detect extensive coronary artery involvement (SNTAX score ≥ 23). The present study showed that the HEART score has a moderate and positive correlation with the SYNTAX score and HEART score with a cut-off value of 6 is a predictor for SYNTAX score of ≥ 23.